ALLERGIC PATHOLOGY AND CELIAC DISEASE — MECHANISM OF COMMUNITY AND DIFFERENCES - M.O. Revnova (Педиатрическая фармакология, 2010)
The article is devoted to the differentiation of allergic diseases and celiac in children. It covers in detail the mechanisms of the pathogenesis of immune inflammation in celiac disease, clinical picture with the main and additional symptoms and markers of this pathology. In the article the author shares data of her own experience and provides the own diagnostic algorithm.Key words: allergic pathology, celiac disease, children. (Pediatric Pharmacology. – 2010; 7(1):76-80)